2015
DOI: 10.1038/nphys3579
|View full text |Cite
|
Sign up to set email alerts
|

Nature of the quantum metal in a two-dimensional crystalline superconductor

Abstract: Two-dimensional (2D) materials are not expected to be metals at low temperature due to electron localization [1]. Consistent with this, pioneering studies on thin films reported only superconducting and insulating ground states, with a direct transition between the two as a function of disorder or magnetic field [2][3][4][5][6]. However, more recent works have revealed the presence of an intermediate quantum metallic state occupying a substantial region of the phase diagram [7-10] whose nature is intensely deb… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

46
310
2
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 278 publications
(363 citation statements)
references
References 37 publications
46
310
2
5
Order By: Relevance
“…It has been known for a long time 32,33 that threedimensional stacking structure of 2H-NbSe 2 is metallic at room temperature and undergoes a CDW transition at 33 K before becoming a superconductor 34,35 at 7.2 K although there has been the controversy regarding on the origin of CDW and the competition between CDW and superconducting (SC) states 32,33,[36][37][38][39][40][41][42][43][44][45] . After a few earlier attempts to investigate physical properties of its thin flakes 1,46,47 , a couple of recent works have reported successful isolations of its single layer form on top of various substrates and measure their CDW and SC phase transitions [27][28][29][30][31] . While all experiments [29][30][31]46,47 hitherto have shown that the superconducting transition temperature decreases but does not diminish completely when the thickness of 2H-NbSe 2 decreases to a single layer limit, the transition temperature (T CDW ) from metal to CDW phase differs from each other significantly 30,31 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been known for a long time 32,33 that threedimensional stacking structure of 2H-NbSe 2 is metallic at room temperature and undergoes a CDW transition at 33 K before becoming a superconductor 34,35 at 7.2 K although there has been the controversy regarding on the origin of CDW and the competition between CDW and superconducting (SC) states 32,33,[36][37][38][39][40][41][42][43][44][45] . After a few earlier attempts to investigate physical properties of its thin flakes 1,46,47 , a couple of recent works have reported successful isolations of its single layer form on top of various substrates and measure their CDW and SC phase transitions [27][28][29][30][31] . While all experiments [29][30][31]46,47 hitherto have shown that the superconducting transition temperature decreases but does not diminish completely when the thickness of 2H-NbSe 2 decreases to a single layer limit, the transition temperature (T CDW ) from metal to CDW phase differs from each other significantly 30,31 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the substrate screening also changes the nature of Coulomb interactions in graphene on top of either dielectric materials or metals and hence modifies the bands further 13,18 . Besides graphene, several recent experiments have revealed new interesting physical properties in a monoand a few-layer TMDs such as series of phase transitions and novel superconductivity, being different from those shown in their bulk forms [19][20][21][22][23][24][25][26][27][28][29][30][31] . Formation of charge density waves (CDWs) in three-dimensional metallic TMDs has attracted interests for the last couple of decades and origins of CDWs in some materials are still not settled yet 32,33 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The suppression of CDW order leads to the emerging superconductivity 1,2 , the CDW coexists with high temperature superconductivity in cupurates 3,4 , and the charge orderings are entangled with colossal magnetoresistance in manganese oxides 5,6 . In recent years, the charge ordering and CDW phenomena coupled with superconductivity are attracting renewed interest for the new functionality of two dimensional transition metal dichalogenides [7][8][9][10] . The recent development of microscopy techniques with the spectroscopic capability such as scanning tunneling microscopy/spectroscopy (STM/S) has made it possible to disclose atomic scale details of charge orderings in complex low dimensional systems in coexistence and competition with various electronic orders.…”
mentioning
confidence: 99%
“…1(b) shows an optical image of a representative device with the MoTe2 flake outlined by a dashed line. In order to avoid the effects of surface oxidation [26][27][28], MoTe2 was exfoliated onto a polymer stamp within a nitrogen-filled glovebox, transferred onto gold electrodes, and covered with hexagonal boron nitride (hBN) before being moved out to the ambient environment. Since hBN conforms to the features of the underlying surface, an atomic force microscope was used to determine the thickness of the buried MoTe2.…”
mentioning
confidence: 99%